Business Model Canvas for local salt business in Bangkala District, Jeneponto Regency (Case Study of Bangkala Ramah Local Salt Business Group) - Muhammad Adam Asgar; Irfan Ramis; Andi Ummung; Andi Nur Apung Massiseng (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
This study aimed to identify the potential of local salt in the Bangkala Ramah salt business group and to analyze the Business Model Canvas of the local salt business in the Bangkala Ramah salt business group, Bangkala District, Jeneponto Regency. Data collection techniques through observation, interviews and documentation. This research was carried out in Minasatene Subdistrict, Pangkep Regency, South Sulawesi Province, from March - June 2022. The results of this study are the potential for people's salt business in the Bangkala Ramah salt business group is Rp. 698,000,000/year, with a total production of 13,960 Kg/year, produced on an area of 9,095 MÂ² with an entire production plot of 107 plots. The results of the Business Model Canvas analysis on the Bangkala Ramah salt business group need improvements to the BMC elements: (1) Customer Segments: added dried fish processors, restaurants, supermarkets, minimarkets, stalls, and traditional markets. (2) Value Propositions: making smaller packaging of coarse salt with its brand and refined iodized salt with its brand. (3) Channels: adding emails as email transactions and data storage. (4) Customer Relationship: forming a salt producer community group. (5) Revenue Streams: income streams from business diversification and invoice generation for marketing administration needs. (6) Key Resources: capital/financial, production machinery and storage warehouse. (7) Key Activities: use production technology and build partner alliances. (8) Key Partnership: Government agencies managing PUGAR and KUGAR throughout Jeneponto Regency. (9) Cost Structure: Transportation rental costs and product storage warehouse rentals.